Backpack ambassadors : how youth travel integrated Europe - Jobs, Richard Ivan (The University of Chicago Press, 2017)
Backpack ambassadors -- Youth mobility and the making of Europe -- Journeys of reconciliation -- Youth movements -- Continental drifters -- East of the wall, south of the sea -- Rights of passage